The Structural Determinants that Lead to the Formation of Particular Oligomeric Structures in the Pancreatic-Type Ribonuclease Family - Benito, A.; Laurents, D. V.; Ribo, M.; Vilanova, M. (Current Protein and Peptide Science, 2008)
Pancreatic-type ribonucleases are a family of RNA degrading enzymes that share different degrees of sequence identity but a very similar 3D-structure. The prototype of this family is bovine pancreatic ribonuclease or ribonuclease A. This enzyme has been the object of landmark work on the folding, stability, protein chemistry, catalysis, enzyme-substrate interaction and molecular evolution. In the recent years, the interest in the study of pancreatic-type ribonucleases has increased due to the involvement of some members of this family in special biological functions. In addition, dimeric and also higher oligomeric structures can be attained by the members of this family. The oligomers described structurally to date are mainly formed by 3D-domain swapping, a process which consists of the exchange of identical domains (i.e. identical structural elements, usually the N- and C-termini) between the subunits and is considered to be a mechanism for amyloid-type aggregate formation. This review compares the dimeric and oligomeric structures of different members of the pancreatic-type ribonuclease family which are able to acquire these structures, namely, bovine seminal ribonuclease, ribonuclease A and its human counterpart, human pancreatic ribonuclease. A specific focus is placed on what is known about the structural determinants that lead to the acquisition of a particular oligomeric structure and on the proposed mechanism of 3D-swapping.
Keywords: protein chemistry